2010
DOI: 10.1371/journal.pone.0013582
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension, Diabetes and Overweight: Looming Legacies of the Biafran Famine

Abstract: BackgroundSub-Saharan Africa is facing rapidly increasing prevalences of cardiovascular disease, obesity, diabetes and hypertension. Previous and ongoing undernutrition among pregnant women may contribute to this development as suggested by epidemiological studies from high income countries linking undernutrition in fetal life with increased burden of non-communicable diseases in later life. We undertook to study the risks for hypertension, glucose intolerance and overweight forty years after fetal exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
253
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(277 citation statements)
references
References 44 publications
23
253
1
Order By: Relevance
“…Wither height in calves at one month of age was positively correlated to mean concentration of glucose. Maternal undernutrition in early pregnancy may cause hypertension in offspring as human adults (Hult et al, 2010;Ravelli et al, 1976) as well as metabolic syndrome (impaired glucose tolerance, hypertension and increased triglycerides) in humans (Barker et al, 1993;Boney et al, 2005;De Rooij et al, 2007;Yarbrough et al, 1998). It is yet to be determined if concentration of glucose in the dam during early gestation might impact calves as they grow and join the lactating herd or whether a method of compensation takes place instead.…”
Section: Discussionmentioning
confidence: 99%
“…Wither height in calves at one month of age was positively correlated to mean concentration of glucose. Maternal undernutrition in early pregnancy may cause hypertension in offspring as human adults (Hult et al, 2010;Ravelli et al, 1976) as well as metabolic syndrome (impaired glucose tolerance, hypertension and increased triglycerides) in humans (Barker et al, 1993;Boney et al, 2005;De Rooij et al, 2007;Yarbrough et al, 1998). It is yet to be determined if concentration of glucose in the dam during early gestation might impact calves as they grow and join the lactating herd or whether a method of compensation takes place instead.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that even children conceived or born at the time of the famine continued to have increased mortality risks during the first few years of life 16. There is also accumulating evidence of chronic disease risks associated with intrauterine exposure to famine, as demonstrated by studies of the Dutch famine in 1944–1945 17, the Chinese famine in 1959–1961 18 and the Biafra famine in 1968–1970 19.…”
Section: Wars Catastrophes and Mortalitymentioning
confidence: 99%
“…Seminal papers by Hult and colleagues (29) at the Karolinska Institute in Sweden, and Fung (30) at Wheaton College in Illinois have shown that malnutrition in early gestation causes greater susceptibility to obesity. Regardless of ethnicity or geographic location, the researchers always observed the effects of famine and the resultant obesity.…”
Section: Environmental Stress and Epigeneticsmentioning
confidence: 99%